Digital DNA in quality control cycles of high-precision products. Issue 1 (2020) - Wagner, Raphael; Haefner, Benjamin; Biehler, Michael; Lanza, Gisela
Abstract: In high-tech production, companies often deal with the manufacture of assemblies with quality requirements close to the technological limits of manufacturing processes. The article shows a digital DNA approach, integrating a digital product twin into the digital twin of the production to enable improved quality control cycles, at organizational level. A statistical meta-model for real-time application is derived from simulation and experimental data. To optimize its performance, its uncertainty according to GUM is minimized. Applying the meta-model, the cyber-physical production system is optimized regarding technical and economic criteria. The approach is demonstrated in an industrial application in the automotive industry.